Field Screening of Arabica Coffee Genotypes against Coffee White Stem Borer (Xylotrechus quadripes) and Leaf Rust (Hemileia vastatrix) Infestation in Kaski, Nepal - Aryal, L.N.; Basnet, S.; Aryal, S. (Journal of Agriculture and Environment, 2022)
Twenty-three coffee (Coffea arabica) genotypes were evaluated for relative resistance against coffee white stem borer (Xylotrechus quadripes) and coffee leaf rust (Hemileia vastatrix) at Horticulture Research Station, Malepatan, Pokhara during three consecutive years from 2016 to 2019. The monthly observation on the emergence of this borer showed that coffee genotypes "Yellow caturra" and “Tekisic” were highly infested with coffee white stem borer as compared to the other genotypes. However, no infestation was observed in genotypes Catimor, San Ramon, Indo Tim-Tim, Ketisic, Pacas, Syangja special and both Vermelo and Amarillo groups in Catui and Caturra acessions. Similarly, genotypes Catimor, Indo Tim-Tim and San Ramon were determined to be resistant to coffee leaf rust. While coffee germplasm- Ketisic was also recorded as relatively resistant against coffee leaf rust. These results have important implications for the development of coffee white stem borer and leaf rust resistant high yielding coffee variety in the future.